การวิจัยชุมชน โดยชุมชนและเพื่อชุมชน ในยุครวมกลุ่มเป็นชุมชนเครือข่ายเศรษฐกิจและสังคมอาเซียน - อดิวัฒนสิทธิ์ จำนงค์ (Academic Journal Phranakhon Rajabhat University, 2016)
วัตถุประสงค์ของบทความชิ้นนี้มีดังต่อไปนี้ เพื่อนำเสนอ 1) วิวัฒนาการศึกษาวิจัยชุมชน 2) รูปแบบการวิจัยชุมชนยุคใหม่ และ 3) การขยายเครือข่ายสัมพันธภาพการวิจัย เพื่อกลุ่มเศรษฐกิจและสังคมอาเซียน การศึกษาวิจัยชุมชนวิวัฒนาการเป็นสี่ยุค โดยตั้งอยู่บนพื้นฐานมุมมองชุมชนของแต่ละยุค ยุคแรกการวิจัยชุมชนเน้นไปที่การแสวงหาความเป็นชุมชนเหมือนกับการมองชุมชนเป็นภาพนิ่ง ยุคที่สองมองชุมชนว่าเต็มไปด้วยปัญหาอันเป็นอุปสรรคต่อการพัฒนาชุมชนสู่ความทันสมัย จำเป็นต้องกำจัดปัญหาและอุปสรรคที่เป็นความเชื่อและประเพณีดั้งเดิมออกไป ยุคที่สามเป็นยุคหวนกลับมามองคุณค่าของชุมชนซึ่งปรากฏอยู่ในรูปของภูมิปัญญาท้องถิ่น และยุคที่สี่เป็นยุคขยายเครือข่ายการพัฒนาชุมชนและความร่วมมือระหว่างองค์กรชุมชน รูปแบบการวิจัยชุมชนรูปแบบใหม่ควรเป็นการวิจัยเชิงปฏิบัติการแบบร่วมมือกันอย่างมีศักดิ์ศรี โดยประชาชนในชุมชนเป็นผู้ร่วมมือเพื่อชุมชนและเมื่อมีการเปิดสัมพันธภาพทางเศรษฐกิจ สังคม และวัฒนธรรมของกลุ่มประชาคมอาเซียนอย่างเสรีในปี 2558 ควรมีการส่งเสริมความร่วมมือกันระหว่างสถาบันการศึกษาระดับสูงในภูมิภาคเพื่อการพัฒนาการวิจัยชุมชนร่วมกัน ซึ่งจะนำมาสู่สัมพันธภาพเครือข่ายการวิจัยชุมชนอย่างสร้างสรรค์ และเป็นประโยชน์ต่อการพัฒนาวิชาการอย่างยิ่ง แม้จะมีบริบททางสังคม วัฒนธรรม และการเมืองที่แตกต่างกันก็ตาม The objectives of this article are to present the evolution of the community research, model of the community research in a new age and the expansion of the network of the community research relationship for the ASEAN Economic and social group. The community research has evolved into four ages based on perspectives on the community in each age. The first age of the community research emphasized the attempt to find out the statehood of the community by looking at the community on the static picture. The second age viewed the community as full of problem and obstacles to develop the community towards modernity. In this age, traditional beliefs and practices were regards on major obstacles which must be eliminated. The third age took a reverse turn towards the community, longing for the value of the community existing in the form of local wisdom. The last fourth age has upheld the expansion of the network for community development and mutual cooperation away the community organizations. The new model of the community research should be a dignified cooperative action research (CAR) by the community partners, who should have a mutual cooperation for the community. Upon a free opening of economic, social and cultural relationship of the ASEAN community in the year 2015, there should be a promotion for a mutual cooperation among high-level educational institutions in the region for the purpose of development of joint community research, that would bring about the network relationship of a creative community research, useful to an identical academic development even though a different social, cultural and political context exists.